(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
This article analyzes the zoohygienic conditions in cattle housing facilities (barns), particularly focusing on microclimatic indicators such as temperature, relative humidity, air movement speed, concentrations of harmful gases (carbon dioxide, ammonia, hydrogen sulfide), and the level of illumination. Detailed information is provided on the methods, instruments, and measurement points used to determine the microclimate. In addition, normative indicators established for housing cattle of different ages and types are compared and studied. According to the research results, it is emphasized that strict adherence to zoohygienic requirements in barns is essential to ensure the health and productivity of animals.